А History of Russian Literature: Foreign Scholars about the Russian Novel (A review of the book by Andrew Kahn, Mark Lipovetsky, Irina Reyfman, And Stephanie Sandler. A History of Russian Literature. Oxford University Press, 2018. 960 p.) (Филологический класс, 2022)
The article presents a review of the book “A History of Russian Literature” published in 2018 by Oxford University Press. It contains an overall description of the publication, which has more than a thousand pages, but pays special attention to the history of Russian literature of the 19th century – the chapter that has become the center of the entire book. It is noted that the authors of the publication under review associate the significance of the Russian literature of the 19th century with the development of the novel. The book analyzes the interpretation of the concept of the Great Russian Novel and the methodological trap that the researchers find themselves in. The path to the great Russian novel is shown in the book in three aspects: personality psychology, social (class) issues, and national identity. Much attention is paid to the ability of the realistic novel to address the issues of the development of the self-consciousness of the nation.